CREATING INTERACTIVE TEACHING LITERATURE IN THE ISPRING PROGRAM (Web of Technology: Multidimensional Research Journal, 2024)
Currently, the breadth of use of mobile teaching aids is the need to create mobile teaching programs, didactic learning resources, teaching programs, courses and control tests. In view of these requirements, the ispringsuite8 program provides information on how to create an interactive educational resource.